Are two‐stage hepatectomies associated with more complications than one‐stage procedures?. Issue 6 (28th November 2012) - Schadde, Erik; Slankamenac, Ksenija; Breitenstein, Stefan; Lesurtel, Mickael; De Oliveira, Michelle; Beck‐Schimmer, Beatrice; Dutkowski, Philipp; Clavien, Pierre‐Alain
Abstract Background Two‐stage liver resections with portal vein occlusion have become standard in patients with low volume future liver remnants. Whether they are associated with more complications is unclear. The aim of this study was to compare complications of one‐ and two‐stage resections in a retrospective study. Methods Patients with two‐stage right liver resections with a previous portal vein occlusion were compared with patients with one‐stage right liver resections between 2002 and 2010. Primary endpoints were the incidence of complications by severity. Secondary endpoints were mortality, post‐operative liver‐ and kidney function tests, length of hospitalization and transfusion events. Logistic and linear regression analyses were performed to adjust for confounders. Results The groups were comparable except for right trisectionectomies, pre‐operative chemotherapy and underlying liver disease. Overall complications occurred in 25 out of 35 patients with two‐stage and 106 out of 163 in one‐stage procedures. Severe complications were observed in 47 out of 163 patients versus 9 out of 35 patients, respectively. Two‐stage procedures had no increased adjusted risk for complications [relative risk (RR) 0.9, P = 0.79]. Mortality (5.7% versus 3.7%) and post‐operative liver failure rates (2.9% versus 3.1%) were low. Secondary endpoints showed no adjusted differences in risk. Conclusion This study suggests that liver resections in two stages are not associated with more post‐operative complications than one‐stage resections. These results should support the adoption of two‐stage liver resections in selected patients.